Catalist: Un museo a tutto tondo, dedicato alla chimica e all’industria chimica - Domenici, Valentina (Chimica nella Scuola, 2023)
This brief contribution aims to describe my visit to the science center ‘Catalyst’, the first interactive science museum dedicated to Chemistry in Europe. The museum is located in the suburb of Liverpool in UK. Thanks to the various interactive hands-on exhibits and to the laboratory areas at the second flour, Catalyst is visited by many school classes and families from UK every year.